Redes de educação ambiental: um meio como proposta pedagógica para o mundo entrelaçado - Carvalho, Néri Andréia Olabarriaga (2007)
The networks terminology has been growing in different meanings, in which emergent structures coming from one not so recently typology aquired, in the 90 s, fluid shapes impelled by waves without borders of the New Information and Communication Technologies. Ever since, the pattern and the morphology are being multiply and strengthen. With this backdrop, this study deals with the Education for Environment Networks, as a political and social, educative and cultural alternative intervention, as an answer for some contemporary demands. But what are these networks? In wich way they organize themselves to germinate political actions? Where is the core of these actions? What are their limits or potentialities? These are some of the questions that are presented along the study proposed. Therefore, we have in view to unveil the network social and environmental pedagogic dimension, as an alternative proposal towards to the planetary cintzenship formation for persons and coletivity. The study employs the exploration reasearch as the analysis of the organizational reference basis and the dinamics of conections that support the dialogue among the groups that belong to the Education for Environment Networks. We conclude that the networks overcome themselves as a powerfull tool to articulate and moblize people. They establish a potential pedagogic act for political and social intervention, as an alternative proposal for the citizen formation and his world vision. We sinalize that the networks are sometimes limited by the poorness of knowledge that still remains on those who find themselves twisted on them, and on the decreasing optics by those who are absent.